1994
DOI: 10.2136/sssaj1994.03615995005800010019x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Response to Organic Amendments and Decreasing Inorganic Nitrogen Rates in Soils froma Long‐Term Experiment

Abstract: To decrease the potential for adverse environmental impacts of N in agroecosystems, there is increasing emphasis on improving N efficiency of organic and inorganic sources. Greater reliance on organic N sources can cause short‐term crop yield decreases. Consequently, a study was conducted to determine the effect of decreasing rates of inorganic N during a transition from inorganic to organic N sources. The approach was to grow four crops of maize (Zea mays L.) during a period of 306 d in the greenhouse on soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In comparison with AN, the CM showed a complete incapacity to provide enough N for maize, the first crop after manure application in the pot experiment. Low apparent N recoveries of farmyard manures are the results usually found in previous studies (Rodrigues et al, 2001;Paul and Beauchamp, 1993;Beauchamp, 1986;Baldock and Musgrave, 1980;Fauci and Dick, 1994).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In comparison with AN, the CM showed a complete incapacity to provide enough N for maize, the first crop after manure application in the pot experiment. Low apparent N recoveries of farmyard manures are the results usually found in previous studies (Rodrigues et al, 2001;Paul and Beauchamp, 1993;Beauchamp, 1986;Baldock and Musgrave, 1980;Fauci and Dick, 1994).…”
Section: Discussionsupporting
confidence: 79%
“…Douglas and Magdoff (1991), working with 19 different organic residues, concluded that organic substrates with C:N ratios between 11 and 25 are usually found to result in net N mineralization. Other studies have shown that apparent N recovery from manures is usually low (Beauchamp, 1986;Paul and Beauchamp, 1993;Fauci and Dick, 1994;Rodrigues et al, 2001). However, Veg showed a long period of apparent net N immobilization which is not usual.…”
Section: Discussionmentioning
confidence: 96%
“…Eghball, (2002) also reported higher SOM with application of compost than with non -composted treatments. The trend observed for soil nitrogen and phosphorus was similar to that of SOM, the positive influence of combined poultry manure + NPK 20 -10 -10 and cowpea (ITAS EARLY) had on soil nutrient dynamics corroborates the results reported by Owaiye (1993); Fauci and Dick (1994) and Eghball, (2002). This seems to suggest that SOM is paramount in sustaining other soil quality factor (Robinson et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, commercial organic fertilizer, poultry manure and fish meal were used for organic treatment. Instantaneous efficiency -that is, rapid mineralizationof these organic materials might be a reason for the short period of low yield (Bitzer and Sims 1988;Fauci and Dick 1994a;Hartz and Johnstone 2006) and/or a reason why N uptake was not a factor responsible for the low yield of organic carrots. Relatively high soil N availability in the experimental field might be another reason for it (Fig.…”
Section: Discussionmentioning
confidence: 99%